Heritabilitas Hasil Pemurnian Galur Harapan Mentimun (Cucumis sativus L.) Kecil Berwarna Hijau Sedang Generasi 4 - Asahak, Alif Ibnu Sina; Rajiman, Rajiman; Fauziah, Nicky Oktav (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Currently, the market demand for cucumber (Cucumis sativus L.) is high, but productivity is declining due to the limited availability of quality seeds. Therefore, a sustainable plant breeding program is necessary to produce superior, high-quality varieties. This research aims to determine the heritability and clustering of promising cucumber lines (Cucumis sativus L.) with a medium green color in the fourth generation. The study was conducted from December 2024 to February 2025 at the Teaching Factory Celeban Polbangtan Yogyakarta-Magelang in Tahunan, and Umbulharjo District, Yogyakarta City, Special Region of Yogyakarta, at coordinates 7°48'17